2009
DOI: 10.1074/jbc.m109.005520
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Trypsin Induces Pancreatic Acinar Cell Death but Not NF-κB Activation

Abstract: Premature intracellular activation of the digestive enzyme trypsinogen is considered to be the initiating event in pancreatitis. However, the direct consequences of intracellular trypsin activity have not previously been examined. In the current study, a mutant trypsinogen (paired basic amino acid cleaving enzyme (PACE)-trypsinogen), which is activated intracellularly by the endogenous protease PACE, was developed. This new construct allowed for the first time direct examination of the effects of intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
66
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 39 publications
9
66
0
Order By: Relevance
“…The two appear to be independent of one another (21,28), but we found that calcineurin is a mediator of both of these pathways. Understanding the mechanisms by which calcineurin targets protease activation and NF-B translocation will form the basis of future work.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The two appear to be independent of one another (21,28), but we found that calcineurin is a mediator of both of these pathways. Understanding the mechanisms by which calcineurin targets protease activation and NF-B translocation will form the basis of future work.…”
Section: Discussionmentioning
confidence: 67%
“…NF-B-Luciferase Activity Assay-Acinar cells were infected with Ad-NF-B-luciferase 24 h prior to stimulation using a previously described procedure (28). Following a wash with DMEM/F12 media, acinar cells were evenly distributed in a 48-well plate and incubated for 30 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Collagenase provides gentle, selective digestion of the intercellular matrix, but is unable to completely disassociate organ tissue into single cells (Gross et al, 1974). Trypsin can disassociate tissue fragments at 37 °C more effectively than collagenase, but can also activate pancreatic zymogens and induce widespread tissue damage and impair viability (Amsterdam and Jamieson, 1974;Ji et al, 2009). These features of warm collagenase and/or trypsin digestion of the adult pancreas cause instability of cell yield and viability, which hampers the isolation and analysis of pancreatic stem/progenitor cells.…”
Section: Introductionmentioning
confidence: 99%
“…The significant involvement of NFkB in inflammatory function has been well established during the last decade. The new insight is that NFkB activation occurs before trypsinogen activation in early AP (4). In addition, local and systemic complicated AP could be induced by activation of adenovirus-transfected NFkB with intraductal injection to acinar cells in genetically modified mice (11).…”
Section: Pathophysiologymentioning
confidence: 99%
“…Whether both are involved or are independently-acting parallel factors in AP is controversial. It was shown, in vitro, that trypsinogen expression did not activate NFkB (4). Conversion of trypsinogen to trypsin within the pancreas is a pathological phenomenon.…”
Section: Pathophysiologymentioning
confidence: 99%